The 1st International Workshop on the Quality of Geodetic Observation and Monitoring Systems (QuGOMS'11) : Proceedings of the 2011 IAG International Workshop, Munich, Germany, April 13–15, 2011 /: Proceedings of the 2011 IAG International Workshop, Munich, Germany, April 13–15, 2011. ([2015]) - Unknown
No abstract available